2018
DOI: 10.18502/jhs.v6i2.45
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Type 1 Diabetes in Children of Mazandaran Province

Abstract: Introduction: The prevalence of type 1 diabetes in all countries throughout the world is different. In this study, an introduction is, therefore, provided for the development of type 1 diabetes in children in Mazandaran province by using all available resources.Methods: In this descriptive cross-sectional study, the prevalence of patients with initial diagnosis of type 1 diabetes mellitus, aging from 6 months to 18 years, was located through contacting and referring to all organizations of insurers and doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In a prospective study that was carried out in Fars province from 21 March 1991 to 20 March 1996, the incidence of type 1 diabetes mellitus among the population aged <30 years was reported to be 3.7 in 100,000, with a significantly higher incidence rate in girls than boys 20 . In another study in Mazandaran, the prevalence of type 1 diabetes mellitus was reported to be 48 in 100,000 among the population aged 18 years 18 . In one recent study from Fars Province, Amiri et al 19 reported the incidence of type 1 diabetes mellitus using the insurance archived prescription for 2 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a prospective study that was carried out in Fars province from 21 March 1991 to 20 March 1996, the incidence of type 1 diabetes mellitus among the population aged <30 years was reported to be 3.7 in 100,000, with a significantly higher incidence rate in girls than boys 20 . In another study in Mazandaran, the prevalence of type 1 diabetes mellitus was reported to be 48 in 100,000 among the population aged 18 years 18 . In one recent study from Fars Province, Amiri et al 19 reported the incidence of type 1 diabetes mellitus using the insurance archived prescription for 2 years.…”
Section: Discussionmentioning
confidence: 94%
“…Providing an epidemiological feature of the disease is a priority for each community for proper allocation of healthcare resources and developing prevention studies. Considering that there were few studies in this field in Iran [17][18][19][20] , we aimed to determine the incidence rate of childhood type 1 diabetes mellitus in Isfahan province and its trend over a period of 12 years. Our findings would help plan nationwide studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes (T1DM) is one of the major endocrine disorders in childhood (2). Recent study in Iran showed that it occurs in 48 cases per 100000 people (50 and 36 cases per 100000 girls and boys, respectively) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Specific CVB serotypes are shown to be related to each of the disorders listed above. As an example, CVB3 infections are linked to viral myocarditis and DCM (6) , CVB5 infections are linked to encephalitis and aseptic meningitis outbreaks (7) , and CVB1 is linked to the induction of β-cell autoimmunity, which is linked to T1DM (8) . In type one diabetes, beta cells are destroyed by an antibody that affects the pancreas, leading to the loss of insulinproducing beta cells (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosing T1DM from other forms is particularly important in its treatment because it helps with medication selection, evaluation of illness prognosis, and determining the risk of diabetes development in family members of the diabetic patient. T1DM is distinguished from other forms by the presence or absence of insulin production (8) . A large number of autoantibodies have been discovered in pancreatic beta cells, and it has been postulated that these autoantibodies may act significant roles at the beginning of autoimmune islet destruction (7) .…”
Section: Introductionmentioning
confidence: 99%